A Study of Knowledge, Experience, and Beliefs About Hepatitis B Virus (HBV) Infection in South Western Uganda - Mugisha, Joseph; Mokaya, Jolynne; Bukenya, Dominic; Ssembajja, Fatuma; Mayambala, Denis; Newton, Robert; Matthews, Philippa C.; Seeley, Janet (Frontiers in Public Health, 2019)
Introduction: United Nations sustainable development goals aim for the elimination of viral hepatitis as a public health threat by 2030, leading to efforts to upscale the availability and accessibility of hepatitis B virus (HBV) vaccination, diagnosis, and treatment globally. However, a variety of societal factors, including beliefs, traditions, and stigma, can be a major obstacle to all of these interventions. We therefore set out to investigate how HBV is understood and described in communities in Uganda, and whether there is evidence of potential stigma. Method: We carried out a qualitative formative study in two sites in South Western Uganda: a village in Kalungu district (site A) and an area on the outskirts of Masaka town (site B). We undertook a rapid assessment to investigate how adults describe HBV infection and their perceptions about the infection. We collected data by conducting a transect walk, observations, community group discussions, and in-depth interviews, sampling a total of 131 individuals. We used inductive content analysis to extract key themes associated with HBV. Results: There is no specific word for HBV infection in local languages, and knowledge about this infection is varied. While some individuals were completely unfamiliar with HBV infection, some had heard of HBV. Radio was a common source of information. There was awareness of HBV as a cause of liver disease, but limited knowledge regarding the cause, mode of transmission, and treatment. Stigma in HBV may be rare in this community due to limited understanding and experience of HBV. Conclusion: There is an ongoing need to improve awareness and understanding of HBV in this community. Careful dissemination of accurate information is required to promote acceptance of interventions for prevention, diagnosis, and treatment.